2008
DOI: 10.32398/cjhp.v6i1.1290
|View full text |Cite
|
Sign up to set email alerts
|

Core human values and their interactions with pro-Tobacco factors on cigarette smoking

Abstract: More effective tobacco control requires new data on factors that are not explicitly related to smoking but are influential, such as “Terminal Values” regarding desirable end-states of existence and “Instrumental Values” regarding desirable modes of conduct. Association analysis was conducted among 36 Core Values (18 Terminal and 18 Instrumental) derived from Rokeach’s Value Survey, three risk factors (protobacco media, smoking peers and sensation-seeking), and cigarette smoking using data collected from a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Data collection was conducted in classroom settings using the “Chinese Student Health Behavior Questionnaire.” Data collectors distributed the questionnaire to individual students in the classroom; participating students completed the survey by themselves with instruction and supervision only by the trained data collector. This questionnaire was developed and used in previous research with adolescent students in China (Chen, Tang, Li, Stanton, & Li, 2008). Participants completed the questionnaire in approximately 25 to 35 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection was conducted in classroom settings using the “Chinese Student Health Behavior Questionnaire.” Data collectors distributed the questionnaire to individual students in the classroom; participating students completed the survey by themselves with instruction and supervision only by the trained data collector. This questionnaire was developed and used in previous research with adolescent students in China (Chen, Tang, Li, Stanton, & Li, 2008). Participants completed the questionnaire in approximately 25 to 35 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Feedback from participants was used in item revision to generate the BSSS-C items. The original BSSS items were taken from the Chinese translation we tested in two previous studies (Tang et al, 2005; Chen et al, 2008). Results from the two studies were not reported because of high rates of missing data for several items and low reliability of the scale (alpha ranged between 0.48 and 0.63).…”
Section: Methodsmentioning
confidence: 99%
“…Questions used to measure the smoking behaviors were based on our previous research in China (Chen et al, , 2008Mao et al, 2009) and with reference to questions used in surveys among youth in the US (e.g. the National Survey on Drug Use and Health, and the California Youth Tobacco Survey).…”
Section: Variables and Measurementmentioning
confidence: 99%